Avaliação da resistência de variedades de milho a Dalbulus maidis (Delong & Wolcott) (Hemiptera: Cicadellidae) - Souza, Ruana Regina Negrão de Souza (Universidade Federal de São Carlos, 2023)
The corn leafhopper, Dalbulus maidis (Delong & Wolcott) (Hemiptera: Cicadellidae) is an important pest in corn crops, capable to cause direct damage through its feeding, and dissemination of three important phytopathogens to corn plants: Maize Bushy Stunt Phytoplasma (MBSP), Spiroplasma kunkelii and Maize Rayado Fino Virus (MRFV). The use of insect-resistant plants is a sustainable and strategically efficient control method for controlling pests and diseases. The objective of this work was to evaluate the resistance of different varieties of creole corn to Dalbulus maidis. The attractiveness of corn plants to D. maidis for food and/or shelter and the preference for oviposition with and without choice was verified. The antibiosis tests verified the effects on the development of the stages of D. maidis in the different varieties, based on the parameters: nymphal period, period from egg to adult, nymphal mortality and insect longevity. The damage caused by D. maidis to corn plants was verified, as well as the responses of corn varieties to MBSP infection. The “IAC AIRAN” and “Amarelo Astecão” varieties presented the highest averages of adult preference compared to “Pipoca Roxo Kika”, which was the least preferred. D. maidis females, in the no-choice test, oviposited more in the “Al Bandeirante” variety compared to “Amarelo Astecão”, which had the lowest average number of eggs. For oviposition tests with a chance of choice, there was no statistically significant difference. In the antibiosis tests, the insects fed on “NS 90 PRO 2” presented the longest nymphal period and the insects in “Pipoca Roxo Kika”, the longest period of development, compared to the insects in “Branco Pedro 2”. The insects in “Amarelo Laleska”, “Amarelo Astecão”, “NS 90 PRO 2”, “Pipoca Roxo Kika” and “Vermelho Pedro” showed the lowest longevity compared to insects from “Al Bandeirante”. In the tolerance test, the percentage growth data and visual scale of damage did not show a statistically significant difference. In tests on plant response to phytoplasma infection, it was shown that 100% of “Pipoca Roxo Kika” plants died, 60% of “Al Bandeirante”, “Amarelo Laleska”, “Branco Pedro 2” and “NS 90 PRO 2” plants did not show any apparent symptoms, 20% showed mild symptoms of yellowing and/or reddening and tillering and the other 20% died. Regarding plant heights, the averages did not show statistically significant differences. After applying a multivariate statistical test, a dendrogram was obtained that indicated the formation of two main groups, which can be characterized as the groups of susceptible varieties and resistant varieties. Therefore, the results of this research may have found sources of resistance in corn plants, which can help control D. maidis, as some varieties stood out for presenting characteristics that directly interfere with the reproduction and development of the insect pest, which can contribute to the choice of materials to be cultivated in the field, in addition to guiding corn genetic improvement programs for plant resistance to insects.
Evaluation of resistance of corn varieties to Dalbulus maidis (Delong & Wolcott) (Hemiptera: Cicadellidae)
Evaluación de resistencia de variedades de maíz a Dalbulus maidis (Delong & Wolcott) (Hemiptera: Cicadellidae)
Keywords: Antixenose; Antibiose; Cigarrinha-do-milho; Milho crioulo; Tolerância; Antixenosis; Antibiosis; Corn leafhopper; Creole corn; Tolerance; CIENCIAS AGRARIAS::AGRONOMIA